Design and modeling of MEMS SAW resonator on Lithium Niobate - Ramli, Noor Amalina; Nordin, Anis Nurashikin (2011)
Surface Acoustic Wave (SAW) resonators are essential components for modern communication systems. They can function as filters and frequency synthesizers. SAW resonators operate based on the principle of acoustic waves propagating along the surface of a solid piezoelectric material. The waves are generated by injecting electrical energy using interdigitated transducers (IDTs) into the piezoelectric material which transforms it into propagating mechanical waves. This project intends to study the key design parameters that affect the performance of SAW resonator such as optimum spacing between IDT and reflector, optimum spacing of IDTs and the numbers of reflector in order to get the highest mechanical displacement. Key requirements of a SAW resonator include having precise resonant frequency (fr), low insertion losses, and high quality factors (Q). To meet these requirements, it is necessary to investigate the key design parameters; number of reflectors, number of IDTs, periodic distance of transducer fingers ( #x03BB;), spacing between IDT and reflector. Finite element simulations to determine the optimum SAW resonator design was performed using COMSOL Multiphysics #x2122;.